LGBTQ+ people living with dementia: an under-served population. (2nd October 2020) - Cousins, Emily; de Vries, Kay; Dening, Karen Harrison
ABSTRACT: Background: Lesbian, gay, bisexual, transgender and queer (LGBTQ+) people living with dementia are an under-served population. They are often at greater risk of vulnerability, discrimination, loneliness, health inequalities and poorer health outcomes. Aims: The aim of this applied practice paper was to produce an introductory summary of some of the challenges and considerations facing LGBTQ+ people living with dementia. This is the second in a series of clinical articles on dementia in underserved populations. Methods: A literature overview was undertaken comprising a number of literature searches. Salient academic articles, policy papers and third sector reports were analysed to identify themes. Findings: Three main themes emerged from the analysis regarding LGBTQ+ people living with dementia: an increasing awareness of needs; challenges and considerations; and recommendations for improving practice and care. Conclusions: Challenges and considerations facing LGBTQ+ people living with dementia include living with memory problems, remembering the past, reminiscence, personal relationships and receiving care. Recommendations include comprehensive training for health and care professionals, as well as strengthened peer support networks. Areas for future research to fully understand the needs of this under-served population are also suggested.